A Dual Zinc plus Arginine formulation protects against tumor necrosis factor-alpha-induced barrier dysfunction and enhances cell proliferation and migration in an in vitro gingival keratinocyte model. (June 2021) - Ben Lagha, Amel; Yang, Ying; Trivedi, Harsh M.; Masters, James G.; Grenier, Daniel
Highlights: TNF-α damaged the barrier function in a gingival keratinocyte in vitro model. Dual Zinc plus Arginine formulation contains zinc oxide, zinc citrate and arginine. The formulation protected against the TNF-α-induced damage. The formulation promoted the proliferation and migration of gingival keratinocytes. The Dual Zinc plus Arginine formulation may offer benefits for oral health. Abstract: Objective: To investigate the effects of Dual Zinc plus Arginine formulations (aqueous solution and dentifrice) on tumor necrosis factor-alpha (TNF-α)-induced barrier dysfunction as well as on cell proliferation and migration in an in vitro gingival keratinocyte model. Design: Gingival keratinocytes were seeded onto the membrane of a double-chamber system in the absence and presence of recombinant TNF-α and the formulations under investigation. The barrier function was assessed by determination of transepithelial electrical resistance (TER) and paracellular transport of fluorescein isothiocyanate (FITC)-dextran. The distribution of zonula occludens-1 (ZO-1) and occludin was visualized by immunofluorescence microscopy. The effects of the formulations on keratinocyte cell proliferation were determined using a fluorescent cell tracker dye, while a migration assay kit was used to investigate their effects on cell migration. Results: Under conditions where TNF-α induces loss of keratinocyte barrier integrity, the Dual Zinc plus Arginine formulations (aqueous solution and dentifrice) protected the keratinocyte tight junction against the damages since they prevented the TNF-α-induced drop in TER and increase in FITC-dextran paracellular flux in the in vitro model. The treatment of keratinocytes with the formulations markedly mitigated the altered distribution of ZO-1 and occludin. Both formulations increased the proliferation of keratinocytes and alleviated the negative impact caused by TNF-α. Lastly, the formulations increased the migration capacity of keratinocytes. Conclusions: The ability of the Dual Zinc plus Arginine formulations to protect the barrier integrity of gingival keratinocytes from TNF-α-induced damage and to promote their proliferation and migration suggests that they may offer benefits for oral health.